К расчету ортотропных пластин с учетом бимоментов - Усаров, М. К.; Аскарходжаев, Ш. И.; Шамсиев, Д. К.; Курбанбаев, М. Ш. (Національний технічний університет "Харківський політехнічний інститут", 2022)
Работа посвящена разработке бимоментной теории и метода расчета толстых пластин в рамках трехмерной теории упругости. Приводятся основные соотношения и уравнения движения пластины, построенные относительно сил, моментов и бимоментов, возникающих из-за нелинейности закона распределения перемещений и напряжений по её толщине. В качестве примера расчета рассмотрены изгиб и колебания изотропных и ортотропных пластин. Полученное решение показало эффективность и точность предложенной бимоментной теории при оценке напряженно-деформированного состояния толстых пластин.

Робота присвячена розробці бімоментної теорії та методу розрахунку товстих пластин у рамках тривимірної теорії пружності. Наводяться основні співвідношення та рівняння руху пластини, побудовані щодо сил, моментів та бімоментів, що виникають через нелінійність закону розподілу переміщень та напруг за її товщиною. Як приклад розрахунку розглянуті вигин та коливання ізотропних та ортотропних пластин. Отримане рішення показало ефективність та точність запропонованої бімоментної теорії при оцінці напружено деформованого стану товстих пластин.

The work is devoted to the development of the bimoment theory and the method for calculating thick plates in the framework of the three-dimensional theory of elasticity. The basic relations and equations of motion of the plate are given, constructed with respect to forces, moments and bimoments, arising from the nonlinearity of the law of distribution of displacements and stresses over its thickness. Bending and vibrations of isotropic and orthotropic plates are considered as an example of calculation. The resulting solution showed the efficiency and accuracy of the proposed bimoment theory in assessing the stress-strain state of thick plates.
До розрахунку ортотропних пластин з урахуванням бімоментів
To the calculation of orthotropic plates taking into account bimoments
Keywords: толстая ортотропная пластина; трехмерная теория упругости; бимоментная теория; изгиб и колебания; напряженно-деформированное состояние; товста ортотропна пластина; тривимірна теорія пружності; бімоментна теорія; вигин та коливання; напружено-деформований стан; thick orthotropic plate; three-dimensional theory of elasticity; bi-moment theory